2015
DOI: 10.1371/journal.pone.0144241
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of FOXM1 as a Potential New Target for Melanoma

Abstract: Recent studies have shown that immunotherapies and molecular targeted therapies are effective for advanced melanoma. Non-antigen-specific immunotherapies such as immunocheckpoint blockades have been shown to be effective in the treatment of advanced melanoma. However, the response rates remain low. To improve their efficacy, they should be combined with antigen-specific immunotherapy. Elevated expression of the transcription factor, Forkhead box M1 (FOXM1), has been reported in various human cancers, and it ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 36 publications
(55 reference statements)
3
32
0
Order By: Relevance
“…GO analysis of the RNA-seq revealed enrichment in pathways involved in cell division and proliferation (Figure S3C), consistent with the phenotypic effects of AMIGO2 knockdown. Interestingly, RPPA analysis did not show significant and/or consistent changes in components of the MAPK signaling pathway (Figure S3D), but did reveal significant changes in FOXM1 (Figures S3B and S3E; Table S3), a TF implicated in melanoma proliferation by promoting cell-cycle progression (Bhat et al, 2008; Ito et al, 2016; Miyashita et al, 2015). Thus, our profiling data suggest that AMIGO2 loss results in transcriptional changes affecting proliferation prior to cell death.…”
Section: Resultsmentioning
confidence: 99%
“…GO analysis of the RNA-seq revealed enrichment in pathways involved in cell division and proliferation (Figure S3C), consistent with the phenotypic effects of AMIGO2 knockdown. Interestingly, RPPA analysis did not show significant and/or consistent changes in components of the MAPK signaling pathway (Figure S3D), but did reveal significant changes in FOXM1 (Figures S3B and S3E; Table S3), a TF implicated in melanoma proliferation by promoting cell-cycle progression (Bhat et al, 2008; Ito et al, 2016; Miyashita et al, 2015). Thus, our profiling data suggest that AMIGO2 loss results in transcriptional changes affecting proliferation prior to cell death.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, overexpression of FOXM1 has been linked in poor prognosis in many solid tumor types [7,36]. Previous studies show FOXM1 enhances cell cycle progression by promoting G1 to S and G2 to M phase transitions [37].…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant expression of miRNAs occurs in many types of cancers, some of which function as tumor suppressor genes or oncogenes [6]. Some studies have implied that miRNAs act as crucial modulators for cancer cell migration, proliferation or epithelialmesenchymal transition (EMT) [7][8][9][10][11][12][13][14]. miR-509-5p has been demonstrated to inhibit EMTrelated genes in melanomas [15].…”
Section: Introductionmentioning
confidence: 99%
“…FOXM1 expression has been noted to be constitutively activated in many cancers including melanoma and to contribute to tumorigenesis and chemo-and radio-resistance (5,(7)(8)(9). A series of 10 melanoma cell lines were tested for FOXM1 protein expression by Western blotting with two different FOXM1 antibodies.…”
Section: Constitutive Foxm1 Expression In Melanoma Cell Linesmentioning
confidence: 99%
“…Recently several lines of evidence have lent support to the roles of FOXM1 expression in inducing metastatic melanoma and suppression of FOXM1 via RNA interference, blocking peptides, or chemotherapeutic agents has proven successful in countering tumorigenesis (7)(8)(9)(10). Importantly new evidence has indicated that combined treatment of FOXM1 inhibition with a small molecule inhibitor Siomycin A (SIOA) and irradiation can achieve a higher rate of cell death in glioblastoma cell lines, thus raising the possibility of harnessing FOXM1 inhibitors as a radiosensitizing agent (11).…”
Section: Introductionmentioning
confidence: 99%